Associations of cardiac autonomic function and physical functional capacity with self-rated health in aging population - Sorola, Samu (2021)
How an individual rates her or his own health is an outcome of complex psychological and physiological mechanisms not well known. Self-rated health (SRH) is a subjective clinical survey tool, which associates with health outcomes and a number of biomarkers. Physical functional capacity (PFC) measured as 6-minute walk test (6MWT) walking distance (6MWD) is associated with health outcomes in aging population. Similarly, cardiac autonomic function (CAF) measured as heart rate response to exercise (HRRTE), and heart rate recovery (HRR) associate with health. However, 6MWD, HRRTE, or HRR associations with SRH have not been studied. Thus, the aim of this study is to investigate if CAF measured as HRRTE and HRR and PFC measured as 6MWD associate similarly with SRH. It was hypothesized that SRH's positive association with 6MWD would be stronger than with HRRTE or HRR.